1998
DOI: 10.1002/(sici)1096-9063(199807)53:3<223::aid-ps767>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Rate of transformation of atrazine and bentazone in water-saturated sandy subsoils

Abstract: : When pesticides leach through the soil to the upper groundwater zone, it is important to know whether further transformation occurs before the pumping wells for drinking water are reached. Atrazine and bentazone were incubated (at 10¡C) in Ðve water-saturated sandy subsoils (collected at depths between 1É5 and 3É5 m), simulating the conditions in the Ðeld. In three subsoils with comparatively low pH and intermediate to high redox potential, atrazine was transformed gradually, to leave 1É9%, 6É2% and 17É5% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Under certain conditions these compounds have been reported to be degradable. In other studies, however, investigations of isoproturon degradation showed an initial transformation under aerobic incubations in chalk aquifer material,52 and bentazone was slowly degraded in aerobic but not in anaerobic aquifer samples during a 3.9‐year study 53…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Under certain conditions these compounds have been reported to be degradable. In other studies, however, investigations of isoproturon degradation showed an initial transformation under aerobic incubations in chalk aquifer material,52 and bentazone was slowly degraded in aerobic but not in anaerobic aquifer samples during a 3.9‐year study 53…”
Section: Discussionmentioning
confidence: 74%
“…Several other contributions consider atrazine to be persistent in aquifer conditions 44. 46, 49, 55–59 Conversely, a few investigations have observed aerobic degradation of atrazine60–62 as well as removal of atrazine under anaerobic conditions 53. 63 Although differences in experimental approaches exist between these contributions, they stress the importance of not only investigating aerobic conditions but of also including anaerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…When atrazine was incubated in groundwater‐zone materials with intermediate to high redox potentials (at 10 °C), its rate of transformation was found to be quite low 16. 17 Results from the latter study are summarized in Table 2. Only in subsoil with very low redox potential was atrazine transformed at a reasonable rate, possibly by reductive dechlorination 17.…”
Section: Brief Survey For Three Groups Of Compoundsmentioning
confidence: 97%
“…17 Results from the latter study are summarized in Table 2. Only in subsoil with very low redox potential was atrazine transformed at a reasonable rate, possibly by reductive dechlorination 17. Gamma‐sterilization had no effect on the rapid transformation of atrazine in this subsoil, so the contribution of biotic processes seemed to be small.…”
Section: Brief Survey For Three Groups Of Compoundsmentioning
confidence: 99%
See 1 more Smart Citation